Semiotic Studies of Padlock Meaning on Liliba Bridge in Kupang - Yohanes Paulus Florianus Erfiani; Hesni Neno (Universitas Tidar, 2018)
This study aimed at investigating the meaning of Padlocks hung on the fence of Liliba Bridge in Kupang, East Nusa Tenggara Province. The meaning of the padlocks was analyzed from semiotic’s approach especially Roland Barthes which meanings were seen from denotation, connotation, and myth. This study used qualitative research method. Based on the data analysis, it was concluded that the hanging padlocks had 3 main meanings, (1) the denotation meaning was the couple or teenagers wrote both their names on a padlock, then they locked and hung it on Liliba Bridge; (2) the connotation meaning was the couple or teenagers had analogy their love in a padlock which had their names in order to make their romantic love lasts forever as same as the padlock; and (3) the myth meaning was the teenagers believed and convinced that their love will last forever if they locked the padlocks on the Liliba bridge.